MONEY POLITICS DALAM PEMILIHAN UMUM OLEH BADAN PENGAWASAN PEMILIHAN UMUM: PENGAWASAN TINDAK PIDANA PEMILU - ARAS FIRDAUS (Universitas Quality, 2020)
The practice of money politics is a crime that often occurs during elections. This is a joint concern to supervise legislative candidates who will carry out these actions and participate in rejecting the practice in order to create clean elections. The problem in this research is how the handling of election criminal acts by the election supervisory body and how to prevent them? And supervision in overcoming the crime of money politics? The research method used in this study is juridical normative. This research is analytical descriptive, the purpose of this study is expected to obtain a detailed and systematic description to answer the problem to be examined. The research results show that sanctions given to perpetrators of money politics should be given strict law enforcement. So that criminal law becomes the foremost law in expressing legal issues related to elections.